The dynamics of sliding air bubbles and the effects on surface heat transfer. (December 2015) - Donnelly, B.; O'Reilly Meehan, R.; Nolan, K.; Murray, D.B.
Highlights: Investigated heat transfer enhancement of air bubbles sliding under heated surface. Bubble shape and path fluctuations found to be closely linked to vortex shedding. Local heat transfer coefficients of up to 8 times natural convection levels observed. Cooling structures take form of elliptical regions that overshoot the bubble path. Abstract: Freely rising and sliding bubbles have been found to increase local heat transfer coefficients from adjacent heated surfaces. The latter have been exploited in various industrial applications, such as shell and tube heat exchangers and chemical reactors. Although there is a relatively large body of work on bubbles, only a very small portion of this focuses on sliding bubbles. The current study intends to expand this by understanding both the motion and surface heat transfer characteristics of sliding bubbles. Herein, results are presented on bubbles of 4.75–9.14 mm equivalent spherical diameter sliding under both a heated and unheated surface, inclined at 30 ° relative to the horizontal. The sliding bubble path and shape oscillations are observed by a pair of high speed cameras. The frequency and amplitude of these oscillations are derived from analysis of the acquired images. Heat transfer is measured using a high speed infra-red camera synchronised to the video cameras, which is spatially and temporally aligned with the high speed images, allowing for the relationship between bubble motion and heat transfer to be observed. It has been found that bubbles in the range tested exhibit a sinusoidal motion. This motion is likely linked to the asymmetrical generation and shedding of vortices, with one vortex shed for each half period of path oscillation. It was observed that the bubble shape fluctuations were closely linked to the path oscillations and therefore vortex shedding. At higher bubble volumes, the bubble interface was found to recoil after a vortex is shed. There is little difference between bubble motion on a heated and unheated surface at lower bubble volumes, but at higher volumes a thinning of the bubble tips is observed along with a less-smooth interface, both of which are attributed to the thermal boundary layer at the surface. The bubble drag coefficient is also decreased when the surface is heated. Two-dimensional, time-varying surface heat transfer patterns reveal local heat transfer coefficient enhancements of up to 8 times that corresponding to natural convection levels, while the global surface-averaged heat transfer coefficient was up to twice that of natural convection. The mechanism of this heat transfer enhancement is a combination of forced convection by the sliding bubble and vortices shed at half the bubble path oscillation frequency that draw cool fluid from the bulk towards the surface. In the far wake, these vortices form isolated, elliptical regions of cooling that remain for many seconds after the bubble has passed. Interestingly, there are regions of the bubble wake where the heat transfer coefficient briefly drops below natural convection levels, highlighting the complexities of the fluid mechanics behind multiphase cooling.